2020
DOI: 10.1038/s41467-020-18635-x
|View full text |Cite
|
Sign up to set email alerts
|

Realizing a deterministic source of multipartite-entangled photonic qubits

Abstract: Sources of entangled electromagnetic radiation are a cornerstone in quantum information processing and offer unique opportunities for the study of quantum many-body physics in a controlled experimental setting. Generation of multi-mode entangled states of radiation with a large entanglement length, that is neither probabilistic nor restricted to generate specific types of states, remains challenging. Here, we demonstrate the fully deterministic generation of purely photonic entangled states such as the cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 31 publications
1
74
0
Order By: Relevance
“…This daunting resource overhead can be avoided by instead using sequential generation schemes. References 22,23 put forward such an approach that works well for one-dimensional (1D) graph states 24 and has led to experimental demonstrations 25,26 . However, in the general case where the entanglement structure is more complicated, this method scales exponentially in the size of the target state and can lead to long generation circuits, motivating the search for more efficient approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This daunting resource overhead can be avoided by instead using sequential generation schemes. References 22,23 put forward such an approach that works well for one-dimensional (1D) graph states 24 and has led to experimental demonstrations 25,26 . However, in the general case where the entanglement structure is more complicated, this method scales exponentially in the size of the target state and can lead to long generation circuits, motivating the search for more efficient approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Besse et al experimentally demonstrated how to use transmon qubits to generate entangled photonic qubits at microwave frequencies [1]. Specifically, they showed how to produce 1D photonic graph states.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we consider how to generate two types of microwave graph states: 2D lattice (cluster) states and all-photonic repeater states. Specifically, we address the following three questions: (1) What superconducting circuits can generate these states? (2) Which type of transmon qubit is better, fixed-frequency or tunable-frequency transmons?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of quantum coherence dynamics induced by open nonlinear qubit-photon systems has recently become a significant area that contributes to the development of potential quantum information applications [ 1 , 2 , 3 , 4 , 5 , 6 ]. We can cite as examples of potential applications in quantum teleportation protocol [ 7 ], cryptography [ 8 ], and computation [ 9 , 10 ], generation of entangled states [ 11 ]. Entanglement is an essential quantum information resource in quantum communication [ 12 ], it has been extensively explored theoretically and experimentally [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%